Identification of tumor suppressor miRNAs by integrative miRNA and mRNA sequencing of matched tumor–normal samples in lung adenocarcinoma - Yu, Namhee (Mol Oncol, 2019)
The roles of miRNAs in lung cancer have not yet been explored systematically at the genome scale despite their important regulatory functions. Here, we report an integrative analysis of miRNA and mRNA sequencing data for matched tumor–normal samples from 109 Korean female patients with non‐small‐cell lung adenocarcinoma (LUAD). We produced miRNA sequencing (miRNA‐Seq) and RNA‐Seq data for 48 patients and RNA‐Seq data for 61 additional patients. Subsequent differential expression analysis with stringent criteria yielded 44 miRNAs and 2322 genes. Integrative gene set analysis of the differentially expressed miRNAs and genes using miRNA–target information revealed several regulatory processes related to the cell cycle that were targeted by tumor suppressor miRNAs (TSmiR). We performed colony formation assays in A549 and NCI‐H460 cell lines to test the tumor‐suppressive activity of downregulated miRNAs in cancer and identified 7 novel TSmiRs (miR‐144‐5p, miR‐218‐1‐3p, miR‐223‐3p, miR‐27a‐5p, miR‐30a‐3p, miR‐30c‐2‐3p, miR‐338‐5p). Two miRNAs, miR‐30a‐3p and miR‐30c‐2‐3p, showed differential survival characteristics in the Tumor Cancer Genome Atlas (TCGA) LUAD patient cohort indicating their prognostic value. Finally, we identified a network cluster of miRNAs and target genes that could be responsible for cell cycle regulation. Our study not only provides a dataset of miRNA as well as mRNA sequencing from the matched tumor–normal samples, but also reports several novel TSmiRs that could potentially be developed into prognostic biomarkers or therapeutic RNA drugs.